2022
DOI: 10.3390/plants11213002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lippia alba (Mill.) N.E. Brown Essential Oil on the Human Umbilical Artery

Abstract: Lippia alba is popularly known as lemon balm, with its essential oil (EO) cited for displaying antimicrobial, sedative, and vasorelaxant effects. Yet, its action on isolated human vessels has not been described in the literature. Thus, we evaluated the vasorelaxant effect of essential oil of L. alba (EOLa) on human umbilical arteries (HUA) isolated in organ baths. HUA rings were isolated, subjected to contractions induced by potassium chloride (KCl), serotonin (5-HT), or histamine (HIST) to record the isometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The greater pharmacological potency of ( E , E )-FAR in the electromechanical pathway in HUA directed us to investigate the influence of Ca 2+ and K + ion channels on the vasodilator effect. We observed that ( E , E )-FAR (800 μmol/L) suppressed contractions evoked by Ca 2+ and Ba 2+ ions more effectively than the control nifedipine which, in turn, is a potent inhibitor of Ca 2+ [ 31 ] and Ba 2+ [ 16 , 17 , 19 ] induced contractions in HUA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater pharmacological potency of ( E , E )-FAR in the electromechanical pathway in HUA directed us to investigate the influence of Ca 2+ and K + ion channels on the vasodilator effect. We observed that ( E , E )-FAR (800 μmol/L) suppressed contractions evoked by Ca 2+ and Ba 2+ ions more effectively than the control nifedipine which, in turn, is a potent inhibitor of Ca 2+ [ 31 ] and Ba 2+ [ 16 , 17 , 19 ] induced contractions in HUA.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of K + channels in the vasodilator effect of ( E , E )-FAR was verified after pre-contraction by 5-HT (10 μmol/L) for 15 min followed by pre-incubation (25 ± 5 min) of HUA rings with each of the following blockers at concentrations standardized for umbilical vessel rings [ 19 , 20 ], nonselective TEA (10 mmol/L), TEA (1 mmol/L) for BK Ca channels and K V channels, GLI (10 μmol/L) for K ATP channels, 4-AP (1 mmol/L) for K V channels, or BaCl 2 (500 μmol/L) for K IR channels. Subsequently, concentration-response curves were obtained with ( E , E )-FAR (1 μmol/L to 1 mmol/L).…”
Section: Methodsmentioning
confidence: 99%